Posilování konkurenceschopnosti firmy - Záškodová, Lenka (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Tato diplomová práce se zabývá zhodnocením současné situace firmy IP IZOLACE POLNÁ, s.r.o. v jejím konkurenčním prostředí. Zkoumá konkurenceschopnost firmy na základě provedených analýz. Dle zjištěných skutečností je sestaven návrh činností, které by měli posílit její konkurenceschopnost do dalších let. Práce se skládá z těchto částí: Marketingová východiska k tématu – teoretické vysvětlení pojmů z této oblasti Analýza současné situace – charakteristika firmy, základní informace, analýzy Návrhová část – návrhy na zlepšení konkurenceschopnosti firmy Závěr – shrnutí všech poznatků

This diploma thesis deals with the evaluation of current situation of the company IP IZOLACE POLNÁ, s.r.o. in its competitive environment. It examines the company's competitiveness on the basis of the analyzes. According to the findings proposal consists of activities that should enhance its competitiveness in the coming years. The work consists of: Marketingt on bases – a theoretical explanation of the terms of the area Analysis of current situation – the characteristics of company, background information, analysis Forms part – suggestions for improving the competitiveness of firms Conslusion – summary of findings
Strengthening the Company Competitiveness
Keywords: Konkurenceschopnost; konkurenční výhoda; strategie; trh; zákazník.; Competitiveness; competitive advantage; strategy; market; customer.